Unnatural lives : studies in Australian fiction about the convicts, from James Tucker to Patrick White - Hergenhan, L. T. (Laurence Thomas), 1931- (St. Lucia, Qld. : University of Queensland Press, 1983)
Includes references to the portrayal of Australian Aborigines in various novels dealing with the period of initial colonisation.
Includes index.
Bibliography: p. [197]-206.
Keywords: Australian fiction -- History and criticism; Convicts in literature; Race relations - Representation - Literature; Settlement and contacts; Australia